Increased renal and forearm vasoconstriction in response to exercise after heart transplantation. Issue 3 (September 1993) - Haywood, G A; Counihan, P J; Sneddon, J F; Jennison, S H; Bashir, Y; McKenna, W J
Abstract : OBJECTIVE--To test the hypothesis that the loss of the inhibitory effect of the cardiac ventricular afferent fibres on the vasomotor centre would result in increased vasoconstrictor drive to the forearm and renal vascular beds during supine exercise in heart transplant recipients. DESIGN--Comparison of regional haemodynamic response to exercise in heart transplant recipients and two age matched control groups. SETTING--Regional heart transplant unit. PATIENTS AND METHODS--Orthotopic heart transplant recipients (n = 10), patients with NYHA class II heart failure (n = 10), and normal controls (n = 10) underwent short duration maximal supine bicycle exercise. MAIN OUTCOME MEASURES--Simultaneous measurements were made of heart rate, systemic blood pressure, oxygen consumption (VO2), forearm blood flow, and renal blood flow. Forearm blood flow was measured by forearm plethysmography and renal blood flow by continuous renal vein thermodilution. RESULTS--The peak forearm vascular resistance was significantly greater in the transplant group than in the controls (mean (SEM) 75 (18) v 40 (7) resistance units, p < 0.05). The percentage fall in renal blood flow at peak exercise was significantly greater in heart transplant recipients than in the controls (44% (4%) v 32% (4%), p < 0.05) as was the percentage increase in renal vascular resistance (transplants: 116% (19%) v controls: 78% (17%), p < 0.05). Regional haemodynamics during exercise in the heart failure group were not significantly different from those in the controls. CONCLUSIONS--These findings suggest that surgical division of the cardiac ventricular afferent fibres results in increased vasoconstrictor drive to the kidneys and non-exercising muscle during exercise. This mechanism may contribute to persistent exercise limitation and renal impairment after heart transplantation.